Accrual Trends for Children's Oncology Group Clinical Trials: A Single Center Experience. Issue 7 (October 2020) - Anderson, Bailey; Wolfe, Ian; Muruganand, Ashwath; Mody, Rajen
Abstract : Children's Oncology Group (COG) has been highly successful in improving childhood cancer survival through well-designed multi-institutional clinical trials. However, our center has recognized a decline in the number of enrollments on COG therapeutic clinical trials over recent years. Our single center, retrospective analysis evaluated in detail the patient enrollment rates, annual number of available clinical trials and reason for nonenrollment over the last decade. We found a 61% decrease in enrollment for phase II to III trials of newly diagnosed patients at our center (2011-2018) along a 29% decrease in the number of open COG studies annually. The primary reason for nonenrollment was unavailability of a suitable trial (76%). We also recognized a decrease in number of adolescent and young adult enrollment particularly in the last 8 years (2010-2018); however, the enrollment rate for adolescent and young adults was not substantially different than enrollment of children. The reasons for reduced enrollments are most likely multifactorial and complex. It is imperative that we continue to develop novel clinical studies using a portfolio of federal, investigator-initiated, and industry trials for pediatric oncology patients to continue to advance outcomes, study survivorship, and improve quality of life for these patients.